Intertemporal competitive equilibrium: a computational model of intermediacy in speculative markets - González Gutiérrez, José Javier (2015)
How are prices set in a market economy with decentralized information? How are we able to extract full gains from trade in a competitive market without centrally coordinated price formation and resource allocation? In 1962, separate research efforts proved that neither rationality nor complete information are necessary market conditions to reach competitive equilibrium1 . Behavioral extensions to this framework have shown significant progress towards a coherent model of competitive price formation under varying conditions of decentralized trade and individual rationality. Unfortunately, economics continues to lack a generally valid model of decentralized price formation